2016
DOI: 10.3389/fmicb.2016.00148
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Triad in Bacterial Meningitis: Pathogen Invasion, NF-κB Activation, and Leukocyte Transmigration that Occur at the Blood-Brain Barrier

Abstract: Bacterial meningitis remains the leading cause of disabilities worldwide. This life-threatening disease has a high mortality rate despite the availability of antibiotics and improved critical care. The interactions between bacterial surface components and host defense systems that initiate bacterial meningitis have been studied in molecular and cellular detail over the past several decades. Bacterial meningitis commonly exhibits triad hallmark features (THFs): pathogen penetration, nuclear factor-kappaB (NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 106 publications
3
30
0
Order By: Relevance
“…The IbeA locus was initially identified as a genetic determinant contributing to E . coli invasion of the BBB, one of the hallmark features of this disease [ 4 , 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IbeA locus was initially identified as a genetic determinant contributing to E . coli invasion of the BBB, one of the hallmark features of this disease [ 4 , 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transmigration of PMNs across the BBB is not only crucial for host defense against pathogens, but it may also cause significant damage to the CNS tissues, which results in devastating neurologic sequelae [ 19 ]. The adhesive interactions between transmigrating leukocytes and endothelial cells are well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the activation of the p38 pathway provides a potential advantage for these bacterial pathogens in bacterial meningitis is not fully understood. It has been reported that for bacterial meningitis the triad of bacterial invasion, NF-κB activation, and leucocyte transmigration is important where p38 activation might also play a role [48,49]. However, since CxCL-1 and CxCL-2 protein levels were only partially dependent on p38 activity, there might be another yet unrecognized pathway affected by PTx.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Animal model and human post-mortem studies indicate that disease pathogenesis in PM is characterised by a marked inflammatory response to bacterial invasion in the CSF, rather than an inability to mount an immune response. The inflammatory cascade and cytotoxic effects of host pro-inflammatory mediators 11,12 together with bacterial toxins drive tissue damage characterised by apoptotic neuronal cell injury, raised intracranial pressure (ICP), thrombosis, cerebral oedema, and cerebral ischaemia. 13,14 These findings supported the use of anti-inflammatory agents, such as dexamethasone as adjunct therapies for PM.…”
Section: Text Backgroundmentioning
confidence: 99%